LEGAL PROTECTION FOR CAR RENTAL BUSINESS ACTORS AGAINST RENTERERS WHO ARE IN DEFAULT (Study of Decision Number 32/Pdt.G/2019/PN Btl and Decision Number 1065/Pdt/2023/PT.DKI) - Natassya Fachrina; Dewi Iryani; G. Nyoman Tio Rae (CV. RADJA PUBLIKA, 2025)
The development of the car rental business in Indonesia faces significant legal challenges, particularly related to default by renters. This study aims to analyze the legal protection available to car rental businesses when facing renters who default, by examining two court decisions: Decision Number 32/Pdt.G/2019/PN Btl and Decision Number 1065/Pdt/2023/PT.DKI. The research method used is normative juridical with a case-based approach and a statutory approach. The results show that legal protection for car rental businesses can be achieved through preventive and repressive channels. Preventive protection is carried out through the creation of a comprehensive written agreement, while repressive protection can be achieved through a lawsuit for default or unlawful acts. Both decisions analyzed show that the courts provide legal protection to business owners by punishing renters who default by paying compensation. However, the implementation of this legal protection still faces obstacles, particularly in terms of executing decisions and recovering losses. This study recommends the need to strengthen regulations specifically for the car rental business and improve guarantee mechanisms that can protect the interests of business owners.